ÂŞIK YAŞAR REYHANİ’NİN “VATAN” TEMALI ŞİİRLERİNİN DEĞERLER EĞİTİMİ AÇISINDAN İNCELENMESİ - Ay, Şule (Bahir SELÇUK, 2025)
Since the moment Turkish identity began to take shape throughout the course of history, the fundamental goal of the Turkish nation has been to uphold the homeland, flag, nation, and cultural values. The trasmission of these values to future generations has been diversified over time and institutionalized, particularly through educational institutions. The education system aims not only for academic success but also for raising individuals with a strong national identity, loyalty to their homeland, imbued with human love, respectful of religious values, and attentive to family structure and cultural identity. Educational institutions prioritize not only developing the interests and talents of students and young people but also enabling them to realize themselves and acguire social harmony skills. Within this framework, values education focuses on imparting national, moral, cultural and religious teachings to students. İn values education, every discipline contributes by transmitting its own resources, while Turkish language and literatüre courses support this process through literary works. Among these, the works of minstrels (âşık tradition) are a significant source that contribute to students’ acguisition of values. İn this context, the aim of the study is to examine how values education is addressed in the poems of Âşık Yaşar Reyhani and to reveal which values, particularly in the context of patriotism are emphasized. The necessity of the study stems from the fact that Turkish literatüre, with its deep-rooted heritage, represents a strong source that can contribute to today’s values education. Accordingly a selection of Reyhani’s poems has been analyzed through descriptive method and content analysis, focusing on values related to patriotism. The findings indicate that Reyhani’s poems raise awareness of individual emotions, social responsibility and especially patriotism. Reyhani, by addressing individuals of all ages with his poems and teachings, contributed to values education and played an important role in transmitting cultural heritage.

Türk kimliği, tarihsel süreç içerisinde şekillenmeye başladığı andan itibaren Türk milletinin temel hedefi; vatan, bayrak, millet ve kültürel değerlere sahip çıkmak olmuştur. Bu değerlerin gelecek nesillere aktarımı zamanla çeşitlenmiş ve özellikle eğitim kurumları aracılığıyla kurumsallaşmıştır. Eğitim sisteminde, yalnızca akademik başarıya değil; millî benliğe sahip, adaletli, vatanına bağlı, insan sevgisiyle yoğrulmuş, dinî değerlere saygılı ve aile yapısına önem veren kültürel kimliğe sahip bireylerin yetiştirilmesi hedeflenmektedir. Eğitim-öğretim kurumları, çocuk ve gençlerin ilgi ve yeteneklerini geliştirmenin yanı sıra onların kendilerini gerçekleştirmelerini ve toplumsal uyum becerisi kazanmalarını amaçlamaktadır. Bu doğrultuda değerler eğitimi, öğrencilere millî, ahlaki, kültürel ve dinî öğretileri kazandırmaya öncelik vermektedir. Değerler eğitiminde her disiplinin kendi kaynakları aracılığıyla eğitim-öğretim sağlarken Türk dili ve edebiyatı derslerinde bu aktarım süreci edebî türlerle desteklenmektedir. Bu edebi türler arasında yer alan âşık edebiyatı ve bu gelenekte yer alan şiirler, öğrencilerin değer kazanımına katkı sağlayan önemli bir kaynak niteliğindedir. Bu bağlamda çalışmanın amacı, Âşık Yaşar Reyhani’nin şiirlerinde değerler eğitiminin nasıl işlendiğini incelemek ve özellikle vatan sevgisi ekseninde hangi değerlerin ön plana çıktığını ortaya koymaktır. Çalışmanın gerekçesi ise Türk edebiyatında önemli bir yere sahip olan âşık edebiyatının günümüzde değerler eğitimine katkı sağlacak güçlü bir kaynak olabileceğini göstermektir. Bu doğrultuda Reyhani’nin seçilmiş şiirleri doküman incelemesi yöntemiyle ele alınmış içerik analizi yapılarak değerlere ilişkin öğelerin nasıl işlendiği çözümlenmiştir. Elde edilen bulgular Reyhani’nin şiirlerinde bireysel duygulardan çok halkı bilinçlendirme, toplumsal sorumluluk ve özellikle vatan sevgisi değerini öne çıkardığını göstermektedir. Reyhani, şiirlerinde her yaştan bireye hitap ederek değerler eğitimine katkı sağlarken kültürel mirasın aktarımında da önemli bir rol oynamıştır.
Keywords: Turkish Language and Literature (Other); Türk Dili ve Edebiyatı (Diğer)